Fertility, immigration, and lifetime wages under imperfect labor substitution. (December 2020) - Guest, Ross; Parr, Nick
Abstract: This paper provides new insights into the effect of birth cohort size on cohort lifetime wages and its sensitivity to the future trajectories of immigration and fertility. The main innovation is to relax the typical assumption of perfect substitution of labor by age. The effect of imperfect substitution of labor by age is to qualify the standard result that smaller birth cohorts are likely to enjoy relatively high wages since that result depends on the size of co-worker cohorts. The positive small cohort effect on lifetime wages therefore depends on demographic patterns, which are simulated here through low and high fertility and immigration projections. The analysis applies to actual and projected cohorts for Australia and tests the sensitivity to alternative demographic parameters, and the substitution and discount parameters. The effects of imperfect substitution can amount several percentage points of lifetime wages.